Efecto del extracto seco de passiflora incarnata (maracuyá) en comportamiento psicótico inducido con ketamina en rattus rattus var. albinus - Castrejón Meregildo, Diana Vanessa (2015)
The aim of this study was to determine the effect of dry extract of Passiflora incarnata (passion fruit) in the ketamine-induced psychotic behavior in Rattus rattus var. albinus. Specimens with five groups were formed: White, Control, Problem I, II and Risperidone Problem; white group received physiological saline solution (PSS) 1 mL / kg intraperitoneally (VIP), the other groups received ketamine at doses of 20 mg / kg VIP, all for 20 days. It passed ten days of administering ketamine and / or SSF began to administer treatments; the target and control groups received distilled water 5 mL / kg orally (PO); the problem I and problem II Passiflora incarnata groups received doses of 100 and 500 mg / kg VO; and the risperidone group received 1 mg / kg PO, all treatments were administered for 21 days. To evaluate the psychotic behavior models "open field" and "rota rod" is used in addition histopathological study of the brains of the specimens was performed. The variables analyzed in the "open field" were advanced square, defecation, standing position, interference and self-cleaning; and "rota rod" was the time spent in the scroll bar. After 30 days of treatment he was obtained in the "open field" more hyperlocomotion with increased square advanced in the control group (p <0.05), who received ketamine; while the risperidone group decreased significantly (p <0.05) hyperlocomotion, similar trend is observed with the groups receiving Passiflora incarnata (p> 0.05); standing position in an increase in the control group (p <0.05) was observed, while Passiflora incarnate, risperidone and 500mg / kg significantly reduced (p <0.05) that variable. Regarding the "rota rod", it was verified that the treatments do not alter the motor coordination (p = 0.2264). A histopathological level, both Risperidone as Passiflora incarnata generate a marked recovery of cellular structures. We conclude that Passiflora incarnata present antipsychotic effect, by acting like Risperidone in the tested models